An overview of the wide extent of Tawarruq implementation in Malaysia Islamic banking products - Hasmad, Nurjannah; Alosman, Abdulrahman (Usuli Faqih Research Centre PLT, 2022)
The Shariah financing concept tawarruq is dominating Islamic banking products nowadays. Tawarruq concept is underpinning various Islamic finance and banking products and growing its portfolio proportion year by year in Malaysia Islamic banking and finance industry. This paper aims to give an overview of the wide extent of tawarruq implementation in Malaysian Islamic banking products.This study employs qualitative approach using library research method by examining and analyzing secondary data collected from multiple sources such as journal articles, policy documents, books, resolutions, standards, product disclosure sheets and reports. Results of this paper suggestthat steps taken by official bodies like issuing a much lenient Shariah standards on tawarruq application than other international standard setting bodies like AAOIFI and Council of International Islamic Fiqh Academy by BankNegara Malaysia and establishment of Bursa Suq As-Sila to facilitate tawarruq implementation by Bursa Malaysia is much aiding the applicationof tawarruq concept in Malaysianotwithstanding some issues causing controversies regarding its application. The study also revealed that Islamic banking products such as Islamic personal financing, Islamic home financing, Islamic credit cards and Islamic deposit account are applying tawarruq concept in a wider term in replacing the application of previous Shariah concepts. It is concluded that tawarruq is gaining larger popularity among Islamic finance and banking industry players, however, innovative alterations need to be applied on the current practice of tawarruq to mitigate critiques surrounding it.